ダイ 25 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1984 - 山本, 雄次; ヤマモト, ユウジ; 田中, 定彦; タナカ, サダヒコ; 稲川, 譲; イナガワ, ユズル; 高尾, 俊則; タカオ, トシノリ; Yamamoto, Yuhji; Tanaka, Sadahiko; Inagawa, Yuzuru; Takao, Toshinori (1988)
P(論文) この報告は第25次南極地域観測隊越冬隊気象部門が, 1984年2月1日から1985年1月31日まで, 昭和基地において行った地上及び高層気象観測の結果をまとめたものである。観測方法, 設備, 結果の取り扱い等はほぼ第24次観測隊と同じである。越冬期間中特記される気象現象としては, 次のものがあげられる。1) 5月7-8日に, 5月としては観測史上初の雨が6時間ほど観測された。2) 11月中旬から12月全般にかけ好天が続き, 12月の月間日照時間は594.5時間で累年第1位の多い値を記録した。3)大気混濁度の値が過去に比べ高めに経過し, 年平均値は過去最高値を示した。 This paper describes the results of meteorological observations (mainly surface and aerological) at Syowa Station from February 1,1984 to January 31,1985. Methods and equipment for observations are the same as in 1983. The observed data were sent to World Meteorological Center at Melbourne via Mawson Station according to the WMO Regulations. Remarkable characteristics are as follows : 1) On May 7 to 8,1984,we had rainfall for about 6 hours. Rainfall in May was observed for the first time. 2) Fine weather continued from middle of November to late December. Monthly total amount of sunshine duration of December was 594.5 hours, which was the maximum record at Syowa Station. 3) Atmospheric turbidity was higher than the normals, and annual mean value was the highest since observation had begun at Syowa Station. departmental bulletin paper